Presidential Prerogative Powers in the Judicial Sphere: A Review of Legal Politics in Applying the Separation of Powers - Fuqoha Fuqoha; Hasuri Hasuri; Rivani Arif Rezeki; Silfi Barten (Ajudikasi: Jurnal Ilmu Hukum, 2026)
The President’s authority in the judicial sphere serves as a constitutional link between the executive and judicial branches in Indonesia. Article 14 of the 1945 Constitution of the Republic of Indonesia grants the President the powers to grant pardons, rehabilitation, amnesty, and to abolish sentences. This arrangement demonstrates that Indonesia’s separation of powers is defined by division and delegation, rather than by absolute separation. This study examines the legal policy regulating the President’s prerogative powers in the judicial sphere and investigates the implementation of the trias politica in relation to the rule of law, judicial independence, and constraints on authority. The research utilizes a qualitative, normative legal methodology, including literature review and legislative analysis. The findings show that, while the Constitution distributes power among the executive, legislative, and judicial branches, the President retains constitutionally mandated authority within the judicial domain. Judicial independence is preserved, ensuring autonomy in judicial functions. The President must exercise prerogative powers in the judicial sphere in accordance with constitutional principles and with consideration of input from the legislative and judicial branches. Legal policy may influence judicial power if the boundaries of authority within the separation of powers are not clearly defined.